Effectiveness of ‘Adad And Ma‘dūd Learning Module Based on al-Quran Verses in Enhancing Student Achievement - Ismail, Zawawi; Hussin, Mohamad; Supriyatno, Triyo (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Misconceptions in using â€˜adad and maâ€˜dÅ«d often occur among students of Arabic language. This happens because of the differences in concept between Arabic and Malay grammar. The system of categorisation, concept as well as type of â€˜adad and maâ€˜dÅ«d in Arabic grammar differs from the concepts used by the native language of the learner. This study aimed at testing the effectiveness of a learning module on â€˜adad and maâ€˜dÅ«d based on al-Quran verses for overcoming problems of misconceptions in learning the topic. Previous studies have shown that al-Quran has enough resources for constructing a module related to the topic. Meanwhile the ADDIE approach was found very helpful in helping to construct a learning module on â€˜adad and maâ€˜dÅ«d. Through the suggested phases the module was built by categorising â€˜adad into three groups based on similar characteristics in each group namely same â€˜adad, opposite â€˜adad and neutralâ€˜adad.Â The findings show that application of the module using al-Quran verses in learning was effective in raising student achievement in â€˜adad and maâ€˜dÅ«d. In all sections it was found that enhanced achievement was encouraging. Students made fewer mistakes in matching â€˜adad, in determining matching maâ€˜dÅ«d, in translating sentences containing â€˜adad and maâ€˜dÅ«d as well as better determining the iâ€˜rÄb rules for application. The findings indicate that using a special module is able to overcome the problems in conceptual application among students of second language, especially in topics likely to cause confusion in students